Aspectos jurídicos da não-cumulatividade do PIS e da COFINS - Pace, Evany Aparecida Leitão de Oliveira (2008)
To be a tax consultant in Brazil has never been an easy task. In order to do it safely, one must be able to handle the legislation produced by the Federal Government, by the 26 States, by the Federal District and also by more than 5 thousand Municipalities. The Federal Government, who has always focused on the income taxes, has been using a new tax approach lately, aiming to reach another kind of wealth expression, the revenue and billing taxation instead of the profit taxation. In such context, the non-cumulative regime of PIS and COFINS was born, and soon after that, has been deeply modified over and over again, by so many laws, ruled by other many decrees, interpreted by numerous normative instructions and other acts issued by the tax authorities. This scenario only brings up insecurity for our tax system. This subject was carefully chosen through our professional experience in order to compose the theme of this work, whose purpose is to analyze through science the legal regime of non-cumulativity of the social contribution to PIS and of COFINS. It is a theoretical work, but also presents a pragmatic view, which is an adjective of its author, who, in her daily activities, has to face various practical cases that are brought up from such new tax regime application, that impacts in almost ten per cent the revenues of the corporations